Live and Live-Dead Intraspecific Morphometric Comparisons as Proxies for Seagrass Stability in Conservation Paleobiology - Anderson, Laurie C.; Long-Fox, Brooke L.; Paterson, Audrey T.; Engel, Annette S. (Frontiers in Ecology and Evolution, 2022)
Comparisons of life and death assemblages are commonly used to detect environmental change when historical records of live occurrences are unavailable. Most live-dead comparisons focus on assemblage composition, with morphologic comparisons less explored. Nonetheless, shape can vary within species with environmental variables, including pollution, indicating the potential for morphometric data be a proxy in conservation paleobiology. We explore the potential for geometric morphometric data from live and dead-articulated Stewartia floridana (Bivalvia: Lucinidae) to serve as proxies for seagrass occurrence and stability. The study area is at the northern end of Pine Island in Charlotte Harbor, an estuarine system with substantial seagrass loss in the 20th century and with subsequent partial recovery. The area sampled has had relatively stable seagrass occurrences since at least the early 2000s. Live and dead-articulated S. floridana were collected along two transects through a patchy seagrass meadow, with sampled sites ranging from bare sand to 100% seagrass cover. Dead-articulated specimens also were collected from three adjacent transects. For live specimens, covariation of shape with seagrass taxonomic composition and percent that each species covered at the time of collection was significant based on a two-block partial least squares analysis, although differences in shape between end members (100% Halodule wrightii and 100% Syringodium filiforme) were not, based on multivariate analysis of variance (MANOVA). Instead, specimens from 100% H. wrightii had significantly greater Procrustes variance. Shape of live specimens placed in categories describing seagrass stability over 6 years prior to sampling (reflecting sclerochronologic estimates of maximum longevity) differed significantly based on MANOVA. For live and dead specimens from the same transects, shape differed significantly, but allometric trends did not. In addition, patterns of morphologic variation tied to seagrass stability were detected in dead-articulated valve shape. Dead shells from adjacent transects differed significantly in shape and allometric trend from both live and dead specimens collected together. We infer that the morphometric differences recorded fine-scale spatial and temporal patterns possibly tied to environmental alteration. Therefore, geometric morphometrics may be a powerful tool allowing death assemblages to track seagrass distributions prior to systematic monitoring in areas under high anthropogenic stress through time.